Oral carriage of Candida albicans in murine AIDS. - Deslauriers, N (1997)
Oral candidiasis is a common fungal infection in patients infected with the human immunodeficiency virus (HIV). Although rare at the time of primary HIV infection, it is frequently found throughout the asymptomatic phase and is predictive of progressive immunodeficiency. However, the precise immune defect which results in outgrowth of commensal Candida albicans in HIV infection has not been identified. Mice infected with the Du5H(G6T2) mixture of mouse leukemia viruses develop a syndrome, designated murine AIDS (MAIDS), that has many of the immune abnormalities found in HIV infection. Retrovirus-infected C57BL/6 mice were examined for their ability to resist the development of oral candidiasis from the carrier state established after a self-limiting acute infection and to clear a subsequent secondary inoculum of oral C. albicans. Most of the mice orally colonized with C. albicans and then inoculated with the retrovirus mixture maintained a low-level oral carriage of C. albicans, while 30% of coinfected mice developed recurring 2- to 3-week episodes of acute Candida proliferation, separated by transient recoveries to the carrier state. The frequencies of CD4+ and CD8+ lymphocytes were, respectively, unchanged and significantly decreased (P < 0.05) in both cervical lymph nodes and spleens of coinfected mice compared to the corresponding frequencies in C. albicans-carrying, virus-free, age-matched control animals. Secretion of gamma interferon by concanavalin A (ConA)-stimulated spleen cells from Candida-carrying, retrovirus-infected mice was significantly decreased (P < 0.05) compared to that of C. albicans-carrying, retrovirus-free mice, in accordance with known abnormalities associated with MAIDS. However, production of this cytokine by ConA-stimulated or unstimulated cervical lymph node cells from coinfected mice was enhanced compared to that of virus-free animals colonized with C. albicans. Acquired resistance to reinfection with C. albicans was maintained in retrovirus-infected mice and was associated with a mucosal recruitment of CD8+ cells not observed in control mice. These results suggest that alterations in mucosal immunity which occur in MAIDS differ substantially from defects observed at other sites and that surrogate epithelial defense mechanisms may function locally to limit Candida proliferation.